Randomised controlled trial of urokinase versus placebo for non-draining malignant pleural effusion - Mishra, E; Clive, A; Wills, G; Davies, H; Stanton, A; Al-Aloul, M; Hart-Thomas, A; Pepperell, J; Evison, M; Saba, T; Harrison, R; Guhan, A; et al. (American Thoracic Society, 2018)
Rationale Patients with malignant pleural effusion (MPE) experience breathlessness, which is treated by drainage and pleurodesis. Incomplete drainage results in residual dyspnea and pleurodesis failure. Intrapleural fibrinolytics lyse septations within pleural fluid, improving drainage. Objectives To assess the effects of intrapleural urokinase on dyspnea and pleurodesis success in patients with non-draining malignant effusion. Methods Prospective double blind randomised trial; patients with non-draining effusion were randomly allocated 1:1 to intrapleural urokinase (100,000 IU three doses 12 hourly) or matched placebo. Measurements Co-primary outcome measures: dyspnea (average daily 100mm visual analogue scores over 28 days) and time to pleurodesis failure to 12 months. Secondary outcomes: survival, time in hospital and radiographic change. Main results 71 subjects randomised (36 received urokinase, 35 placebo) from 12 UK Centres. Baseline characteristics were similar between groups. There was no difference in mean dyspnea between groups (mean difference 3·8mm, 95% CI -12 to 4·4mm, p=0·36). Pleurodesis failure rates were similar (urokinase 13/35 (37%), placebo 11/34 (32%), adjusted hazard ratio 1·2, p=0·65). Urokinase was associated with a decreased effusion size on chest radiograph (adjusted relative improvement -19% (95% CI -28 to -11%, p<0·001), reduced hospital stay (1·6 days (95% CI 1·0 to 2·6), p=0·049) and improved survival (69 days versus 48 days, p=0.026). Conclusions Use of intrapleural urokinase does not reduce dyspnea or improve pleurodesis success compared with placebo, and cannot be recommended as an adjunct to pleurodesis. Other palliative treatments should be used. Improvements in hospital stay, radiographic appearance and survival associated with urokinase require further evaluation.